Reading Literacy of Students with Intellectual Disabilities at the End of the Systematic Literacy Development Period - Jenko, Nika; Lipec Stopar, Mojca (Specijalna edukacija i rehabilitacija, 2020)
Developing reading literacy of students with mild intellectual disabilities (hereinafter ID) is one of the more challenging educational issues. These students are usually enrolled in an adapted program with lower educational standards (hereinafter AP LES), which predicts that by the end of the literacy development period the students will have mastered reading techniques to the point of being able to focus primarily on developing reading comprehension. Throughout this research, we were interested in finding out the degree to which this goal was fulfilled in a group of 61 fifth grade students with ID, enrolled in AP LES, at the end of the systematic literacy development period. Using factor analysis, we studied the characteristics of reading literacy in this group of students. Additionally, we compared the results of students with ID with the norms created for students of typical development at the end of their literacy development period (third grade). We can conclude that reading efficiency of students with ID at the end of the literacy development period is still based on lower level processes (decoding). Reading issues of students with ID are complex in nature and apply to various factors of reading literacy. Taking the students’ oral reading accuracy into account, we can reach a conclusion that only a smaller percentage of students is capable of reaching the fundamental goal of reading lessons in the given amount of time. Based on our results we will be able to give suggestions on how to plan future reading lessons in AP LES.